Caspase 1 activity influences juvenile Batten disease (CLN3) pathogenesis. Issue 5 (9th August 2018) - Burkovetskaya, Maria; Bosch, Megan E.; Karpuk, Nikolay; Fallet, Rachel; Kielian, Tammy
Abstract: Juvenile Neuronal Ceroid Lipofuscinosis (JNCL) is an autosomal recessive lysosomal storage disease caused by loss‐of‐function mutations in CLN3 . Symptoms appear between 5 and 10 years of age, beginning with blindness and seizures, followed by progressive cognitive and motor decline, and premature death. Glial activation and impaired neuronal activity are early signs of pathology in the Cln3 Δex7/8 mouse model of JNCL, whereas neuron death occurs much later in the disease process. We previously reported that Cln3 Δex7/8 microglia are primed toward a pro‐inflammatory phenotype typified by exaggerated caspase 1 inflammasome activation and here we extend those findings to demonstrate heightened caspase activity in the Cln3 Δex7/8 mouse brain. Based on the ability of caspase 1 to cleave a large number of substrates that have been implicated in JNCL pathology, we examined the functional implications of caspase 1 inflammasome activity by crossing Cln3 Δex7/8 and caspase 1‐deficient mice to create Cln3 Δex7/8 / Casp‐1 −/− animals. Caspase 1 deletion influenced motor behavior deficits and astrocyte activation in the context of CLN3 mutation, since both were significantly reversed in Cln3 Δex7/8 / Casp‐1 −/− mice, with phenotypes approaching that of wild‐type animals. We also report a progressive age‐dependent reduction in whisker length in Cln3 Δex7/8 mice that was partially caspase 1‐dependent. However, not all CLN3 phenotypes were reversed following caspase 1 deletion, since no significant differences in lysosomal accumulation or microglial activation were observed between Cln3 Δex7/8 and Cln3 Δex7/8 / Casp‐1 −/− mice. Although the molecular targets of aberrant caspase 1 activity in the context of CLN3 mutation remain to be identified, our studies suggest that caspase 1 may represent a potential therapeutic target to mitigate some attributes of CLN3 disease. This article is part of the Special Issue "Lysosomal Storage Disorders" . Abstract : Caspase 1 activity influences juvenile Batten disease (CLN3) pathogenesis. Mutations in CLN3 (ceroid lipofuscinosis 3; Cln3 Δex7/8 ) manifest as a progressive neurodegenerative disorder commonly referred to as juvenile Batten disease. Based on the ability of caspase 1 to cleave a large number of substrates that have been implicated in juvenile Batten disease pathology, we examined the functional implications of caspase 1/inflammasome activity by crossing Cln3 Δex7/8 with caspase 1‐deficient mice to create Cln3 Δex7/8 / Casp‐1 −/− animals. Caspase 1 deletion influenced motor behavior deficits, whisker length, and astrocyte activation in the context of CLN3 mutation, since both were significantly reversed in Cln3 Δex7/8 / Casp‐1 −/− mice, with phenotypes approaching that of wild‐type animals. Although the inducers of aberrant caspase 1 activity in the context of CLN3 mutation remain to be identified, danger‐associated molecular patterns (DAMPs) released from diseased lysosomes and senescent mitochondria are potential candidates (denoted by question marks). Candidate Signal 1 and Signal 2 stimuli that are required for caspase 1 activation and reportedly elevated in the brains of CLN3 patients and CLN3‐deficient mice are indicated. This article is part of the Special Issue "Lysosomal Storage Disorders" .